Pragmatic analysis of refusal strategies in spoken English of Bahraini and Indian L2 learners - Rawan Emad Al-Sallal (Cogent Arts & Humanities)
The present study investigated the pragmatic performance of Bahraini and Indian Second Language (L2) learners. The study explored the influence of factors (gender, social distance, and degree of imposition) on selected refusal strategies, in terms of frequency, number, and order of strategies. The participants of the study were comprised of three groups: 20 Bahraini Learners of English (BLE), 20 Indian Learners of English (ILE), and 12 Native English speakers from America and Britain (NE), equally distributed concerning gender. Role plays and Discourse Completion Test (DCT) was used for data assortment. Data analysis was conducted based on the classification scheme and frameworks proposed by Brown and Levinson and Culpeper. The study findings indicated differences in terms of group sensitivity to social distance, gender, and imposition degree that affected the frequency, number, and order of using pragmatic strategies. Pragmatic transfer in Native Language (L1) was found among the responses of Bahraini and Indian learners, instigated by different communication styles and cultural factors. The results highlight that BLEs, ILEs, and NEs differ significantly concerning cultural influences and communication styles. Different refusal strategies were employed with varied methods of data assortment.